2023
DOI: 10.1002/smll.202300844
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Engineering: From Precise Macromolecular Inks to 3D Printed Microstructures

Abstract: Macromolecules with complex, defined structures exist in nature but rarely is this degree of control afforded in synthetic macromolecules. Sequence‐defined approaches provide a solution for precise control of the primary macromolecular structure. Despite a growing interest, very few examples for applications of sequence‐defined macromolecules exist. In particular, the use of sequence‐defined macromolecules as printable materials remains unexplored. Herein, the rational design of precise macromolecular inks for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Finally, we demonstrated that despite the extremely low concentration compared to other pre-polymer based two-photon microprinting resists 51 , 52 , we were able to print 3D-structures with good feature resolution, and at a relatively large scale. Figure 7 shows two rubber duck structures with a height of 100 μm, fabricated from the T5 -containing resist.…”
Section: Resultsmentioning
confidence: 89%
“…Finally, we demonstrated that despite the extremely low concentration compared to other pre-polymer based two-photon microprinting resists 51 , 52 , we were able to print 3D-structures with good feature resolution, and at a relatively large scale. Figure 7 shows two rubber duck structures with a height of 100 μm, fabricated from the T5 -containing resist.…”
Section: Resultsmentioning
confidence: 89%
“…In nature, the synthesis of biopolymers, such as proteins, DNA, and RNA, exhibits precise control over building blocks, resulting in defined sequence, chirality, and topology, which are crucial for the physiological functions and evolutionary processes of life. On the other hand, while synthetic polymers have greatly influenced the modern society due to the excellent comprehensive performance, they often face challenges of the polydispersity and inconsistent molecular structures. , Therefore, numerous strategies have been developed to refine synthetic polymers at the molecular, supramolecular, and macroscopic levels, to emulate the precision of biopolymers. , Techniques such as coordination polymerization, living anionic or cationic polymerization, , reversible deactivation radical polymerization, and ring-opening metathesis polymerization , have advanced the manipulation of molecular weight to reduce polydispersity . The concept of sequence-defined polymers (SDPs) has also been proposed, which are unique monodisperse synthetic oligomers or polymers, wherein different monomers units are placed in exact positions (i.e., uniform in IUPAC terms). , However, achieving such monodispersity characteristic remains a challenge in synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%